A Review Study of Error Analysis Theory - Al-Khresheh, Mohammad Hamad (International Journal of Humanities and Social Science Research, 2016)
Up until the late sixties, the prominent theory in the field of second language acquisition or learning was almost behaviouristic, which claimed that the learning was a result of acquiring a set of new language patterns. Hence, second language errors were considered as only the result of learners’ mother tongue habits in the target language. Errors which were not explained based on this assumption will definitely be underestimated. Therefore, there was a need for another approach in order to clearly describe second language learners’ errors. Given this, the current study aims at reviewing and discussing the Error Analysis theory in terms of theoretical foundations, theoretical assumptions, limitations and significance of this theory. This review reveals that despite the criticism that this theory has received, it still plays a fundamental role in investigating, identifying and describing second language learners’ errors and their causes. Most importantly, Error Analysis can enable second language teachers to find out different sources of second language errors and take some pedagogical precautions towards them. Moreover, Error Analysis can provide a good methodology for investigating second language learners’ errors. Once the causes or sources of errors are discovered, it is probable to conclude and decide on the remedy.